Notas sobre la conducta y nidificación de la Mosqueta Myiophobus fasciatus en Buenos Aires, Argentina - Fraga, Rosendo Manuel (1983)
The Bran-colored Fiycatcher Myiophobus fasciatus was studied at the southem border of its distribution in Buenos Aires. Data on adult behavior are include different vocalizations were recognized. A total of 11 nest were studied. Nesting success was only 14.30%. Clutch size seems to be about 2 eggs throughout the species range. Variation in the growth rate of nestlings may explain this unusual uniformity, but further information on this point is needed.